PELATIHAN PEMBUATAN PRODUK OLAHAN BERBAHAN SAYURAN UNTUK PENINGKATAN PENDAPATAN KELOMPOK USAHA ARIKA AMA ORY DI NEGERI PASSO, KOTA AMBON - Meilvis Elsworth Tahitu; Inta Prista Novembriyanty Damanik; Syane Palijama (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This activity aimed to provide learning experiences about vegetable-based derivative products to the Arika Ama Ory group to produce various healthy processed vegetable products and subsequently increase the group's income. The method of this activity were socialization and training that begun with needs assessment and pre-test to determine the initial conditions of the knowledge, attitudes, and skills of group members related to processed vegetable products. The participants were all members of the Arika Ama Ory group (12 people). At the end of the activity, a post-test was conducted. Comparison of the pre-test and post-test results showed an increase in the knowledge, attitudes, and skills of group members related to processed vegetable products which was realized through the ability to produce various products, including moringa smoothies, mix smoothies, pear bok choy smoothies, bok choy egg noodles, nuggets and vegetable meatballs. Some recommendations from this activity are: (1) continuous mentoring activities to internalization of behavioural changes that occur during the activity, (2) maintain the continuity of vegetables as processed ingredients, and (3) expand the market through various promotions and digital marketing, as internet access is readily available in this area.